The Role Of Bajarmasin Political Jargon (Barasih Wan Many) In Educing Banjarmasin Communities To Save The Environment - Abdul Khair; Abdul Malik; Muzahid Akbar Hayat; M. Hidayatollah; Yulia Dewi Wulan Sari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The political message conveyed by the local government through its jargon which can be in the form of a political promise or an illustration of a program that will be implemented in the region will become stronger when it is repeated on various occasions. For the past 2 periods, Mayor H. Ibnu Sina has consistently used the Banjarmasin jargon Baiman as a form of political promise with religious nuances adapts to the character of Banjarmasin which is also known as religious. Not only that, Baiman turns out to be an acronym for Barasih Wan Comfortable, which means Clean and Comfortable. The purpose of this research is to understand the forms and channels used by the Banjarmasin city government, especially H. Ibnu Sina, in communicating the Banjarmasin jargon Baiman. The method used in this study is a qualitative approach as a research procedure that produces descriptive data in the form of written or spoken words from people or observed behavior. This approach is directed at the background and the individual as a whole. The results of this study stated that H. Ibnu Sina as the owner of the slogan, the role of the City Government and his assertiveness were also reinforcing factors in the success of the Banjarmasin Baiman slogan in changing people's behavior. The conclusion is that the Banjarmasin Slogan Baiman Barasih wan Comfort has a central role when this sentence is included in the Mayor's Vision and Mission, which later becomes the RPJMD, is passed down to become the Head of Service's Strategic Plan, then becomes a program that is directly felt by the community.